Inflation, income distribution, and x-efficiency theory : a study prepared for the International Labour Office within the framework of the World Employment Programme - Leibenstein, Harvey; International Labour Office; World Employment Programme (London ; New York : Croom Helm ; Barnes & Noble, 1980)
The major aim of this book is to see whether if linkage can be established between such aspects of an economy as its income distribution, the degree of X-efficiency, inflation and the level of employment in the context of a developing society, and to see if any interesting implications result.
Imprint covered by label: Published in U.S.A. by Barnes & Noble, Totowa, N.J.
Includes bibliographical references and index.
osa;28/11/18
Loans
Keywords: Income distribution; Inflation (Finance)